(untitled) (International Seven Journal of Multidisciplinary, 2024)
Among other challenges, embankments on soft soils have inspired geotechnical engineers, designers and executors to seek challenging solutions. Professor Márcio Almeida, one of the greatest experts on the subject, mentions that these challenges have already resulted in successes and memorable failures in works on soft soils. In general, soft soils are considered to be materials with high plasticity, in some cases rich in organic matter, with Nspt ≤ 4. Thus, brief considerations about soft soils are presented, as well as results with analysis and discussion of geotechnical studies carried out on the Boa Vista Western Bypass Highway (BR 174), in the state of Roraima, with the aim of determining the resistance of soils by means of in situ Vane Tests, in accordance with ABNT NBR 10905: 1989 (MB-3122). The studies consisted of carrying out “Geotechnical Field Investigations” on 11 sections of the highway. Considering the results, it was found that the layers of soft soil in the sections studied have “average” thicknesses that vary from section to section, with minimums close to 2.0 meters and maximums that exceed 6.0 meters. In addition, the existing embankments of the old road, located on the sections studied, indicate the presence of soils with low bearing capacity under the body of the embankments. In addition to the studies, solutions are proposed for the embankments on soils with low bearing capacity.